The Investment Climate in South Africa? Regulatory Issues : Some Insights from the High-Growth, Export-oriented SME Sector - Christianson, David (Washington, DC: World Bank, 2012)
Small and medium enterprises in South Africa consider the local investment climate overregulated. The principal problems identified by SMEs are complicated labor regulations, skills development issues, difficulties accessing domestic capital and pressures, including regulations, to pursue an empowerment agenda. Labor regulation burdens in particular affect investment decisions made by SMEs and contribute to capital intensive "jobless" growth. While there may have been good reasons for new regulations to address the distortions of apartheid, this has been done with little reference to principles of regulatory best practice.